(untitled) (Transactions on Additive Manufacturing Meets Medicine, 2020)
In response to the personal protective equipment shortages caused by the COVID-19 pandemic, our team established a collaboration with Orlando Health and Stratasys for the development, validation and mass production of 3D-printed, custom-fit N95 respirators and face shields. The partnership has delivered more than 5000 face shields to local Central Florida hospitals, including Orlando Health and Lakeland Regional.